Resistance genes of Neisseria gonorrhoeae to cefixime and azithromycin - Louisa Ivana Utami; Yeva Rosana (Faculty of Medicine, Universitas Trisakti, 2023)
Gonorrhea is the second most common sexually transmitted bacterial infection (STI), following Chlamydia. Neisseria gonorrhoeae resistant to antibiotics are increasing globally in the world. In recent years, many studies have reported reduced susceptibility of N.gonorrhoeae to almost all clinically useful antibiotics and also reported cases of multi-resistance. Resistance mechanisms for N. gonorrhoeae can occur through genetic and non-genetic changes. Resistance to cefixime and azithromycin as first-line antibiotics for monotherapy recommended by the World Health Organization (WHO) has been reported from several countries. Genetic changes were reported as the main cause of N.gonorrhoeae resistance to cefixime and azithromycin. Based on the WHO and the United States Centers for Disease Control and Prevention recommendations, countries are increasingly using a combination of cephalosporin and azithromycin for the treatment of gonorrhea. The aim of this review is to analyze genetic variation of N.gonorrhoeae resistance to cefixime and azithromycin. Articles published in English in the last 12 years (from 2010 to 2021) were retrieved from Science Direct, PubMed, Springerlink, Oxford and Nature using relevant searching terms. Mutants of cefixime-resistant N.gonorrhoeae are mediated by mosaic and non-mosaic penA genes encoding penicillin binding protein 2. In addition, mutations in the repressor and promoter genes of mtrR were also found that caused overexpression of the microbial efflux pump. Meanwhile, N. gonorrhoeae resistance to azithromycin reportedly occurs through two strategies, namely overexpression of the efflux pump (mutation of the mtrR codon region) and decreased affinity for antibiotics (single base mutation in the 23S rRNA gene). With the limited choice of antibiotics for the management of N.gonorrhoeae, it is necessary to do regular surveillance for monitoring drug resistance. By understanding the mechanism of resistance, the use of these antibiotics can be rationally optimized.